2021
DOI: 10.1002/etc.5118
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Chemicals and Mixtures of Potential Biological Concern Detected in Passive Samplers from Great Lakes Tributaries Using High‐Throughput Data and Biological Pathways

Abstract: Water-borne contaminants were monitored in 69 tributaries of the Laurentian Great Lakes in 2010 and 2014 using semipermeable membrane devices (SPMDs), and This article is protected by copyright. All rights reserved. Accepted Articlepolar organic chemical integrative samplers (POCIS). A risk-based screening approach was used to prioritize chemicals and chemical mixtures, identify sites at greatest risk for biological impacts, and identify potential hazards to monitor at those sites. Analyses included 185 chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Both ToxCast and ECOTOX provide distinct types of information with differing biological coverage and would not always be expected to agree; therefore, prioritization thresholds were established independently for these two sets of screening values. An EAR Chem value >10 −3 was considered to have exceeded a prioritization threshold, consistent with previous similar analyses (Alvarez et al, 2021; Corsi et al, 2019) which found that using an EAR threshold of 10 −3 resulted in a list of prioritized chemicals similar to that of traditional water‐quality benchmarks. A TQ value >0.1 was considered to have exceeded a prioritization threshold, similar to previous analyses (Corsi et al, 2019).…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Both ToxCast and ECOTOX provide distinct types of information with differing biological coverage and would not always be expected to agree; therefore, prioritization thresholds were established independently for these two sets of screening values. An EAR Chem value >10 −3 was considered to have exceeded a prioritization threshold, consistent with previous similar analyses (Alvarez et al, 2021; Corsi et al, 2019) which found that using an EAR threshold of 10 −3 resulted in a list of prioritized chemicals similar to that of traditional water‐quality benchmarks. A TQ value >0.1 was considered to have exceeded a prioritization threshold, similar to previous analyses (Corsi et al, 2019).…”
Section: Methodssupporting
confidence: 83%
“…Several summary metrics are modeled from chemical dose–assay response curves in the ToxCast data analysis pipeline. For the present study, the ACC was chosen for comparison with observed water concentrations, consistent with previous efforts (Alvarez et al, 2021; Blackwell et al, 2017; Corsi et al, 2019; Fay et al, 2018). The ACC is determined as a multiplier of the baseline median absolute deviation of measured activity in the assay that provides an indication of the concentration at which the bioactivity measured first exceeds the baseline response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diheptyl phthalate and tributyl citrate are two high production volume plastic additives that were first identified via suspect and nontarget screening of fine particulate matter and stormwater runoffs, respectively. TBEP is a plasticizer and flame retardant that may possess the potential for endocrine disrupting effects and has been found to accumulate in POCIS deployed in the Great Lakes tributaries . With the exception of TBEP, none of the level 1 nontarget compounds was captured by grab samples despite their widespread detection in streams.…”
Section: Resultsmentioning
confidence: 99%
“…ToxCast provides several summary metrics derived from dose-response curves to indicate chemical potency. Following previous studies (Alvarez et al, 2021;Blackwell et al, 2017;Bradley et al, 2019;Corsi et al, 2019), the present study used the ACC as an indicator of the chemical concentration that may be required for bioactivity to begin occurring in the assay. The ACC is an assay-specific metric determined as a multiplier of the baseline median absolute deviation of measured activity in the assay that provides an indication of the concentration at which the bioactivity measured first exceeds the baseline The sum of the EAR values for all chemicals associated with a common ToxCast assay endpoint concentration.…”
Section: Discussionmentioning
confidence: 99%